Optimal Design Of Reinforced Concrete Counterfort Retaining Walls - Jasim, Nabeel A.; Hameed, Falah Majeed (Basrah Journal for Engineering Sciences, 2012)
Mathematical programming techniques have been used to minimize the cost of reinforced concrete counterfort retaining wall.The study presents a formulation based on elastic analysis and the ultimate strength method of design as per ACI-M318code. A computer program is generated to handle the considered problem. The formulation of optimization problem has been made by utilizing the interior penalty function method as an optimization method with the purpose of minimizing the objective function representing the cost of one-meter length of the counterfort retaining wall. This includes cost of concrete, reinforcement, and formwork. The design variables considered in this study are the dimensions and the amounts of reinforcement. It is found that the optimal spacing of counterforts equals about (0.214 to 0.366) of total height of wall. The optimum width of the base is found in the range (0.50 to 0.78) of the total height of the wall. Also the thickness of the stem is in the range(0.0284 to 0.0377) of the total height and it is less than half thickness of the base.